2020
DOI: 10.3390/nano10122423
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Quantum-Dot Light Emitting Diodes with Alkali Metal Carbonates Blending in Mg Doped ZnO Electron Transport Layer

Abstract: We report here the fabrication of highly efficient and long-lasting quantum-dot light emitting diodes (QLEDs) by blending various alkali metal carbonate in magnesium (Mg) doped zinc oxide (ZnO) (MZO) electron transport layer (ETL). Alkali metal carbonates blending in MZO, X2CO3:MZO, control the band-gap, electrical properties, and thermal stability. This can therefore enhance the operational lifetime of QLEDs. It is found that the conductivity of X2CO3:MZO film can be controlled and the thermal stability of ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…14 Indeed, QLEDs using ZnO NPs doped with the Mg ion as the ETL have achieved remarkable success and have reached efficiencies as high as 20.19% 15 and lifetimes of more than 1 720 000 h. 16 Despite the advantages of Zn 1−x Mg x O NPs as the ETL and the achieved efficiency of QLEDs equivalent to that of organic LEDs (OLEDs), 17−20 many challenges still remain in both scientific research and commercial applications. 21 One of the key issues is to control the reproducibility and size uniformity of In this work, we explored a new method to synthesize Zn 1−x Mg x O NPs using the Corning advanced-flow reactor (AFR). The AFR platform can potentially overcome the issues associated with the traditional one-pot colloidal synthesis method, such as the size nonuniformity, poor reproducibility, and short lifetime in storage.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Indeed, QLEDs using ZnO NPs doped with the Mg ion as the ETL have achieved remarkable success and have reached efficiencies as high as 20.19% 15 and lifetimes of more than 1 720 000 h. 16 Despite the advantages of Zn 1−x Mg x O NPs as the ETL and the achieved efficiency of QLEDs equivalent to that of organic LEDs (OLEDs), 17−20 many challenges still remain in both scientific research and commercial applications. 21 One of the key issues is to control the reproducibility and size uniformity of In this work, we explored a new method to synthesize Zn 1−x Mg x O NPs using the Corning advanced-flow reactor (AFR). The AFR platform can potentially overcome the issues associated with the traditional one-pot colloidal synthesis method, such as the size nonuniformity, poor reproducibility, and short lifetime in storage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the advantages of Zn 1– x Mg x O NPs as the ETL and the achieved efficiency of QLEDs equivalent to that of organic LEDs (OLEDs), many challenges still remain in both scientific research and commercial applications . One of the key issues is to control the reproducibility and size uniformity of Zn 1– x Mg x O NPs.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 There are a number of reports focusing on the stability of ETL as the ZnO-based NCs are chemically active and sensitive to the environment (temperature, oxygen, moisture, etc.). [15][16][17][18] On the other hand, there are obvious differences among the red, green, and blue quantum dots (QDs), especially the relatively higher conduction band maximum of blue QDs. [19][20][21][22][23][24] This may require different ETLs for different color QLEDs, i.e., the patterning of ETL (different ETL materials for different color pixels) is needed.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of reports focusing on the stability of ETL as the ZnO‐based NCs are chemically active and sensitive to the environment (temperature, oxygen, moisture, etc.) 15–18 . On the other hand, there are obvious differences among the red, green, and blue quantum dots (QDs), especially the relatively higher conduction band maximum of blue QDs 19–24 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, such a layer has been incorporated in quantum dot and perovskite light-emitting diodes, either on its own or in combination with another ZnO layer to inject electrons. [38][39][40][41][42][43][44][45][46] Such studies have demonstrated that doping ZnO with Mg can lead to a more balanced injection and therefore an increase in the maximum external quantum efficiency and current efficiency. The improvement has been attributed to a decreased conductivity and an upward shi of the conduction band of the Mg-doped ZnO ETL compared to the undoped ZnO ETL.…”
Section: Introductionmentioning
confidence: 99%